Molecular mechanism of ferroptosis and its role in the occurrence and treatment of diabetes - Du, Guanghui; Zhang, Qi; Huang, Xiaobo; Wang, Yi (Frontiers in Genetics, 2022)
Ferroptosis is an iron-dependent programmed cell death, which is different from apoptosis, necrosis, and autophagy. Specifically, under the action of divalent iron or ester oxygenase, unsaturated fatty acids that are highly expressed on the cell membrane are catalyzed to produce lipid peroxidation, which induces cell death. In addition, the expression of the antioxidant system [glutathione (GSH) and glutathione peroxidase 4 (GPX4)] is decreased. Ferroptosis plays an important role in the development of diabetes mellitus and its complications. In this article, we review the molecular mechanism of ferroptosis in the development of diabetes mellitus and its complications. We also summarize the emerging questions in this particular area of research, some of which remain unanswered. Overall, this is a comprehensive review focusing on ferroptosis-mediated diabetes and providing novel insights in the treatment of diabetes from the perspective of ferroptosis.